Left ventricular diastolic dysfunction in type 2 diabetes mellitus patient without cardiovascular disease: the association with microalbuminuria (Medical Journal of Indonesia, 2005)
Twenty-eight cases of type 2 diabetes mellitus (DM) without any cardiovascular disease were recruited from the Department of Metabolic-Endocrine, Faculty of Medicine, University of Indonesia / Dr. Cipto Mangunkusumo General Hospital, Jakarta. Recruitment of the study began in October 2001 and was completed by December 2001. Participants were examined for echocardiography and microalbuminuria urinary examination. Diastolic dysfunction was found in 73.7% of type 2 diabetic patients without microalbuminuria and 66.7% in type 2 diabetic patients with microalbuminuria. Neither type 2 diabetic groups with nor without microalbuminuria indicated any significant association to the occurrence of diastolic dysfunction. (Med J Indones 2005; 14: 169-72)